CONSTRUCTION OF MEANING IN PHOTOS OF ANI BAMBANG YUDHOYONO IN HER ACTIVITIES AS FIRST LADY THROUGH SEMIOTIC ANALYSIS IN NEWS PHOTOS - Indah Fitriana Hapsari; Novalia Agung Wardjito Ardoyo (International Journal of Social Science, 2025)
Photo is an analog form of a reality, as the first order of a few messages that substance and has no place in developing the second-order message of all structures. The photos on the electronic media is visual studies that have messages that can be constructed. The photos on the activities concerning the study of semiotics Ani Bambang Yudhoyono in May 2009 - May 2011 can be constructed into meanings. The method of this study, usesd Roland Barthes semiotic analysis. The paradigm used in this study is the constructivist paradigm. Study of semiotics that is in use in this study is the method of text analysis to analyze the semiotics of Roland Barthes's on the photo activity occurred between Ani Bambang Yudhoyono with supporters around. The results of this study indicate that the text image of Ani Bambang Yudhoyono divided according to their respective areas of authority, such as relation between Indonesia and other countries, relation between the mother country with the bureaucrats, relation between the mother country with her ​​family, relation between the mother country with the people of Indonesia..